Descriptive Text Writing: Peer Response Strategy and Students’ Learning Motivation - Putra Pratama; Nurfisi Arriyani (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
This quantitative study research is aimed to find out whether or not (1) peer-response strategy gives a significant impact on descriptive text-ability of the students with high and low motivation; and (2) peer-response strategy and students’ motivation gave interaction effect on the students’ descriptive text writing. 2 classes of 10th grade consisting of 30 students each were selected through cluster random sampling as the sample which then being determined to become groups of experimental and control. Both pre-and post-tests of descriptive text writing and a questionnaire to measure students’ motivation in learning were used as the instruments in collecting the data. The statistical analysis of t-test and two-way ANOVA hence used to analyze the data. The findings of this study revealed that: (1) peer-response strategy significantly influence descriptive text-ability of the students either with high or low motivation in which p-output of 0.000 was lower than mean significant difference at the level of 5% (0.05), and (2) the calculation result of p-output which reached the value of 0.142 (higher than significant difference at the level of 5%) showed that there was no interaction effect of peer-response strategy and motivation on students’ descriptive text writing. Thus, this research study concluded that peer-response strategy gave a significant effect on the descriptive text writing ability of the students with both high and low motivation in learning.